A Crosslinked HA-Based Hydrogel Ameliorates Dry Eye Symptoms in Dogs - Williams, David L.; Mann, Brenda K. (International Journal of Biomaterials, 2013)
Keratoconjunctivitis sicca, commonly referred to as dry eye or KCS, can affect both humans and dogs. The standard of care in treating KCS typically includes daily administration of eye drops to either stimulate tear production or to hydrate and lubricate the corneal surface. Lubricating eye drops are often applied four to six times daily for the life of the patient. In order to reduce this dosing regimen yet still provides sufficient hydration and lubrication, we have developed a crosslinked hydrogel based on a modified, thiolated hyaluronic acid (HA), xCMHA-S. This xCMHA-S gel was found to have different viscosity and rheologic behavior than solutions of noncrosslinked HA. The gel was also able to increase tear breakup time in rabbits, indicating a stabilization of the tear film. Further, in a preliminary clinical study of dogs with KCS, the gel significantly reduced the symptoms associated with KCS within two weeks while only being applied twice daily. The reduction of symptoms combined with the low dosing regimen indicates that this gel may lead to both improved patient health and owner compliance in applying the treatment.